2011
DOI: 10.4317/medoral.17327
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Occlusal ART Restorations in Primary Molars Placed in School Environment and Hospital Dental Setup-One Year Follow-up Study

Abstract: Objective: The objectives of this clinical study were to: evaluate the survival of occlusal atraumatic restorative treatment (ART) restorations, on a longitudinal basis, in the primary molars of children; and compare the success rate of ART restorations placed in school environment and in hospital dental setup. Study design: One dentist placed 120 ART restorations in 60 five-to seven year-olds who had bilateral matched pairs of carious primary molars. A split-mouth design was used to place restorations in scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Other variables, such as the environment (clinic or field) and the moisture control method (cotton roll, saliva ejector, or rubber dam) had no effect on the success rate of ART restorations. 40 Roshan and Sakeenabi 41 evaluated the success rate of ART restorations placed in a school setting and a clinical dental setup and concluded that there was no statistically significant difference between the ART restorations in both assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Other variables, such as the environment (clinic or field) and the moisture control method (cotton roll, saliva ejector, or rubber dam) had no effect on the success rate of ART restorations. 40 Roshan and Sakeenabi 41 evaluated the success rate of ART restorations placed in a school setting and a clinical dental setup and concluded that there was no statistically significant difference between the ART restorations in both assessments.…”
Section: Discussionmentioning
confidence: 99%